Hyaluronan and RHAMM in Wound Repair and the “Cancerization” of Stromal Tissues - Tolg, Cornelia (Hindawi Publishing Corporation, 2014)
Tumors and wounds share many similarities including loss of tissue architecture, cell polarity and cell differentiation, aberrant extracellular matrix (ECM) remodeling (Ballard et al., 2006) increased inflammation, angiogenesis, and elevated cell migration and proliferation. Whereas these changes are transient in repairing wounds, tumors do not regain tissue architecture but rather their continued progression is fueled in part by loss of normal tissue structure. As a result tumors are often described as wounds that do not heal. The ECM component hyaluronan (HA) and its receptor RHAMM have both been implicated in wound repair and tumor progression. This review highlights the similarities and differences in their roles during these processes and proposes that RHAMM-regulated wound repair functions may contribute to “cancerization” of the tumor microenvironment.